English Students Belief on Learning English Through Self-Recording Video - Prayudha. S, Joko (Journal of English Teaching and Linguistic Issues (JETLI), 2023)
Technological developments in the world of education provide enormous opportunities to improve students' abilities independently. The use of technology also provides an opportunity for students to be able to search for and learn from various sources without having to deal with the teacher directly. Therefore, this study examined students' perspectives on their English speaking ability through self-recorded videos they made. This opinion can be divided into two parts, namely, the advantages and disadvantages of implementing English learning using self-recorded videos. The method used in this research is qualitative through a descriptive approach. Furthermore, data was obtained through observation of learning activities and interviews regarding deeper perceptions of self-recorded videos. The results of the study show that students have positive views and changes towards increasing their self-confidence in communicating in English; they are also more courageous in providing ideas, creativity, and better speech. However, there are also drawbacks faced by students related to self-project videos, including inadequate technological devices, lack of ideas and reference sources for making videos, internet quota, and amount of time to complete the project. However, even though they experienced challenges in processing their English, their communication skills had improved quite well.